Subnational Foreign Relations of West Java and Guangxi Zhuang in Human Resource Development: A Case Study of the Teacher Training Program in Nanning - Veruschka, Moza; Dermawan, Windy (Indonesian Journal of Social Science Research, 2025)
This study examines the subnational cooperation between West Java Province and Guangxi Zhuang Autonomous Region in the field of human resource development, particularly through a teacher training program in Nanning. Against the backdrop of globalization and decentralization, regional governments are increasingly pursuing international collaborations to meet local development needs. Through a qualitative descriptive method and secondary data analysis, this research explores how the Sister Province Memorandum of Understanding, renewed in 2023, facilitated a vocational teacher training program focused on electric vehicle technologies. The program provided participating teachers with both technical skills and industrial exposure, aligning West Java’s vocational education with global industry trends. Results indicate that the cooperation has contributed to curriculum renewal, improved pedagogical practices, and fostered institutional reforms in vocational schools. It also led to the formation of joint coordination mechanisms and strategic planning efforts to ensure sustainability. While the training initiative has shown concrete results, the study notes that long-term success depends on continuous evaluation, broader school participation, and stronger public-private linkages. This case highlights how paradiplomacy can serve as a strategic tool for addressing localized capacity gaps through international educational exchange. The West Java–Guangxi Zhuang partnership demonstrates that subnational actors are capable of designing and managing development-oriented foreign cooperation with measurable outcomes. It offers a model for other regions aiming to internationalize technical education and build resilient human capital through structured, inclusive, and policy-driven paradiplomatic efforts.